2005
DOI: 10.1158/1055-9965.epi-04-0918
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Is a Risk Factor for Cervical Intraepithelial Neoplasia Grade 3 among Oncogenic Human Papillomavirus DNA–Positive Women with Equivocal or Mildly Abnormal Cytology

Abstract: Background: Smoking is a potential risk factor for cervical cancer and its immediate precursor, cervical intraepithelial neoplasia grade 3 (CIN3), but few studies have adequately taken into account the possible confounding effect of oncogenic human papillomavirus (HPV) infection. Methods: Women (n = 5,060) with minimally abnormal Papanicolaou smears were enrolled in the ASCUS and LSIL Triage Study, a clinical trial to evaluate management strategies, and were seen every 6 months for the 2-year duration of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
70
3
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 31 publications
8
70
3
7
Order By: Relevance
“…Unlike most previous research in this field, our study showed that current cigarette smoking was not related to the risk of cervical cancer, while exposure to passive smoke seemed to be related to the risk of CIN 2/3. Although a consistent association between cigarette smoking and cervical cancer has been noted in numerous studies (22,23), the relationship between smoking and cervical cancer is difficult to prove. This is because of the strong confounding effect of sexual behavior, such as number of sexual partners and exposure to other sexually transmitted diseases.…”
Section: Discussionmentioning
confidence: 97%
“…Unlike most previous research in this field, our study showed that current cigarette smoking was not related to the risk of cervical cancer, while exposure to passive smoke seemed to be related to the risk of CIN 2/3. Although a consistent association between cigarette smoking and cervical cancer has been noted in numerous studies (22,23), the relationship between smoking and cervical cancer is difficult to prove. This is because of the strong confounding effect of sexual behavior, such as number of sexual partners and exposure to other sexually transmitted diseases.…”
Section: Discussionmentioning
confidence: 97%
“…Tobacco smoking is independently associated with risk of cervical cancer in case-control studies, and risk of cervical dysplasia among HPV-infected women increases with intensity and duration of tobacco use. [26][27][28] However, it remains unclear whether this increased risk is due solely to the independent genotoxic effects of tobacco-related carcinogens or whether tobacco exposure also affects the natural history of cervical HPV infection. Tobacco-related immune dysfunction might facilitate an incident HPV infection among exposed individuals, impede the ability to clear an infection, or facilitate reactivation of a latent infection.…”
Section: Discussionmentioning
confidence: 99%
“…20 Smokers are less likely to clear HPV infection and have an increased risk for cervical neoplasia. 21,22 Interesting correlates of vaccine acceptance were also seen when men's sexual history was examined. Men who were not currently sexually active were more likely to want the HPV vaccine.…”
Section: Discussionmentioning
confidence: 99%